Investigating information literacy levels among primary and secondary school students: A survey-based study - Yang, Houqi; Zheng, Fengqiong (American Journal of Education and Learning, 2025)
In the rapidly evolving digital society, information literacy has emerged as a critical competency for primary and secondary school students, directly influencing their academic performance and future development. This study investigates the information literacy of students in grades 4 to 9 across five nine-year compulsory education schools in Zigong City, aiming to provide insights for developing scientific and effective training programs. The research combines questionnaires with interviews to collect data from 2,000 students, with statistical analysis conducted using SPSS22.0 software.Key findings indicate that students' information literacy is generally at a moderate level, with significant correlations observed among four dimensions. Students demonstrate relatively balanced performance across these dimensions, though information ethics scores are slightly lower compared to others.It means their information literacy exsits several challenges, including insufficient information awareness, gaps in information knowledge depth, uneven development of information abilities, and deficiencies in information ethics practices. To address these challenges,including optimizing information technology curricula, enhancing teacher training, improving parental involvement, and purifying the social information environment. Future research could further explore the specific mechanisms influencing students' information literacy and adapt to emerging technological trends to better support educational practices. This study contributes to the understanding of information literacy development among primary and secondary school students and offers practical recommendations for educators and policymakers to foster digital-age competencies.